The Oceans - Barton, Robert (Chicago Ferguson Publishing Company, 1980)
This book has been released under two titles "Secrets of the Oceans" and "The Oceans" but is the same book. It's an illustrated encyclopedia of marine sciences of 336 pages , published by the excellent Facts on File company and written by Robert Barton. Chapters information on ocean size, waves, currents, tides and marine life as well as the latest advances in fishing, il and gas exploitation, power generation from the oceans and a look into the future to see how ocean resources could be developed further and what international problems might arise from such development. It ha terrific maps and graphics and is lavishly illustrated with color photos on every page. This is Oceanography made easy for teens and adults and has detailed sections on marine life, submersibles, submarines, deep sea diving suits and much more. Originally published at 24.95, this large book maintains its value from its well written approach that makes science accessible and fascinating.
Keywords: Oceanography